Planning and analyzing DVB-T technology in Pulo Aceh using high altitude platform station - Rizal Munadi; Anwar Siddiq; . Roslidar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Abstact. The development of telecommunication technologies has shown remarkable improvement rapidly in this decade, one of which is in information computer and telecommunication technology. On the other hand, the services can be provided with the advance of information technology has not reached all levels of society. In Indonesia, geographic and demographic factors are among the obstacles that limit the dissemination of information. This generally occurs in remote areas such as Pulo Aceh region. To solve the problem, this study proposes a solution to overcome the isolation of information. The technology chosen for the dissemination of information is the Digital Video Broadcasting-Terrestrial (DVB-T) using High Altitude Platform Station (HAPS) technology to provide the services. The implementation of HAPS technology is expected to be able to be used as an alternative for minimizing the high cost of terrestrial infrastructure investment. This discussion is devoted to the planning of implementing HAPS in Pulo Aceh to serve the needs of communication to that community. Based on ITU recommendation, the results show that the analysis of link budget calculation with elevation angle, 34.060 has met the standard requirement. It can be concluded that Pulo Aceh can be served by a single HAPS both in terms of capacity and coverage area.